Mitragynine (Kratom)-induced cognitive impairments in mice resemble Δ9-THC and morphine effects: reversal by cannabinoid CB1 receptor antagonism - Ismail, Nurul Iman; Ahmad, Nur Aimi Zawami; Mohd Yusof, Nurul Aiman; Talib, Ummi Nasrah; Norazit, Anwar; Kumar, Jaya; Mehat, Muhammad Zulfadli; Hassan, Zurina; Muller, Christian P.; Muzaimi, Mustapha (Frontiers Media, 2021)
Kratom is a widely abused plant-based drug preparation with a global interest in recent years, well beyond its native grounds in Southeast Asia. Mitragynine, its major psychoactive constituent is known to exhibit opioid-like behavioral effects with resultant neuroplasticity in the brain reward system. Its chronic administration is associated with cognitive impairments in animal studies. However, the underlying molecular mechanism for such a deficit remains elusive. In this study, the involvement of cannabinoid type-1 (CB1) receptors in cognitive deficits after chronic mitragynine exposures was investigated for 28 days (with incremental dose sensitization from 1 to 25 mg/kg) in adult male Swiss albino mice using the IntelliCage® system. Chronic high-dose mitragynine exposure (5–25 mg/kg, intraperitoneal [i.p.]), but not low-dose exposure (1–4 mg/kg, i.p.), induced hyperlocomotion, potentiated the preference for sucrose reward, increased resistance to punishment, and impaired place learning and its reversal. Comparable deficits were also observed after chronic treatments with Δ-9-tetrahydrocannabinol (THC, 2 mg/kg, i.p.) or morphine (5 mg/kg, subcutaneous). Mitragynine-, morphine-, and THC-induced learning and memory deficits were reversed by co-treatment with the CB1 receptor antagonist, NIDA-41020 (10 mg/kg, i.p.). A significant upregulation of CB1 receptor expression was found in the hippocampal CA1 region and ventral tegmental area after chronic high-dose mitragynine and morphine, whereas a downregulation was observed after chronic THC. In conclusion, the present study suggests a plausible role of the CB1 receptor in mediating the dose-dependent cognitive deficits after chronic high-dose mitragynine exposure. This also highlights the potential of CB1 receptor antagonism in ameliorating the cognitive deficits associated with long-term kratom/mitragynine consumption in humans.